Synthesis and evaluation of the antibacterial activity of Cu(II) and Ni(II) complexes with mixed ligands based on glycine and dicarboxylic acids - Luisa Fernanda Múnera-Gómez; Juan Carlos Muñoz-Acevedo; Elizabeth Pabón-Gelves (Dyna)
A large number of metal complexes have the ability to inhibit bacterial growth. Cu(II) and Ni(II) complexes based on glycine (Gly), itaconic acid (Ita), and oxalic acid (Ox) were synthesized by conventional methods and evaluated for their antibacterial activity. The metal complexes were characterized by TGA, FTIR, UV-vis spectroscopy, and XRD. The metal: ligands (M:L1:L2) stoichiometry of these complexes is 1:2:2, and coordination around Cu(II) and Ni(II) seems to be octahedral, with the ligands bound through the N atom of the amino group and O atoms of the bridging carboxylate group. These compounds are crystalline and stable at temperatures between 250 to 300°C. The metal complexes were screened for their antibacterial activity against the bacterial species Staphylococcus aureus, Bacillus cereus, Listeria monocytogenes, Salmonella, and Escherichia coli. These compounds were shown to have antibacterial activity mainly against gram-positive strains, with a minimum inhibitory concentration of 20 ppm.